Analysis of the Implementation of Public Services in an Electronic-Based Government System (Mataram City Study) - Lalu Rakhmat Suryaningrat; Siti Hasanah; Firzhal Arzhi Jiwantara; Nurjannah Septyanun (International Journal of Health, Economics, and Social Sciences (IJHESS), 2025)
This research aims to analyze the laws and regulations on the electronic-based government system in Mataram City as an effort to improve fast, efficient and affordable public services and to describe the implementation of applications in public services in Mataram City and formulate relevant solutions. Normative-empirical research with legislative, conceptual and sociological approaches in qualitative descriptive analysis, the data used are primary, secondary and literature research materials and field research. Dto conclude; First, SPBE in the government system is needed in order to provide better service to the community, which in principle has been regulated in Presidential Regulation Number 95 of 2018 concerning Electronic-Based Government Systems. And second, the Mataram City Regional Government is committed to implementing electronic-based public services, namely with the issuance of Regional Regulation Number 3 of 2020 concerning the Implementation of Electronic-Based Government Systems and Mataram Mayor Regulation Number 20 of 2024 concerning Guidelines for the Implementation of SPBE. And through Diskominfo, it has managed 14 information technology services with each service application effectively